Radiation exposure to anaesthetists during endovascular procedures1. (30th September 2014) - Arii, T.; Uchino, S.; Kubo, Y.; Kiyama, S.; Uezono, S.
Summary Medical radiation exposure increases the likelihood of cataract formation. A personal dosimeter was attached to the left temple of 77 anaesthetists during 45 endovascular aortic aneurysm repairs and 32 interventional neuroradiology procedures. Compared with interventional neuroradiology, the median (IQR [range]) total radiation dose emitted by fluoroscopic equipment was significantly lower during endovascular aortic aneurysm repair (4175 (3127–5091 [644–9761]) mGy than interventional neuroradiology (1420 (613–2424 [165–10 840]) mGy, p < 0.001). However, radiation exposure to the anaesthetist's temple was significantly greater during endovascular aortic aneurysm repair (15 (6–41 [1–109]) μSv) than interventional neuroradiology (4 (2–8 [0–67]) μSv, p < 0.001). These data suggest that anaesthetists at our institution would have to deliver anaesthesia for ~1300 endovascular aortic aneurysm repairs and ~5000 interventional neuroradiology cases annually to exceed the general occupational limits, and ~10 000 endovascular aortic aneurysm repairs and ~37 500 interventional neuroradiology cases to exceed the ocular exposure limits recommended by the International Commission on Radiological Protection. Nevertheless, anaesthetists should be aware of the risk of ocular radiation exposure, and reduce this by limiting the time of exposure, increasing the distance from the source of radiation, and shielding.